Big markets for small companies - Enderwick, Peter (Henry Stewart Talks, 2009)
Assessment of the opportunities and challenges facing smaller countries and firms when doing business in the large emerging markets of Asia, Importance and challenges of exporting, Attraction of emerging markets in Asia, Challenges of doing business in large emerging markets, Alternative entry strategies, Exporting assistance